Bridging Fluorine and Aryne Chemistry: Vicinal Difunctionalization of Arynes Involving Nucleophilic Fluorination, Trifluoromethylation, or Trifluoromethylthiolation - Zeng, Yuwen; Hu, Jinbo (Synthesis, 2016)
Multi-functionalized fluorinated arenes, especially those that are transformable fluorinated building blocks, are intriguing compounds in synthetic chemistry and for life science related applications. The development of straightforward and efficient approaches to these compounds is of significant importance and has, therefore, attracted much attention. This short review presents our recent progress on the fluoro-difunctionalization of arynes, which allows facile construction of a series of fluorinated arene building blocks bearing an ortho-iodine substituent as a coupling handle for further elaboration.1 Introduction2 Silver-Mediated Trifluoromethylation–Iodination of Arynes3 Silver-Catalyzed Insertion of Aryne into Rf–I Bonds4 Diphenyliodonium-Catalyzed Fluorination of Arynes5 Silver-Mediated Trifluoromethylthiolation–Iodination of Arynes6 Summary and Outlook
Keywords: aryne; fluorine; trifluoromethylation; fluorination; trifluoromethylthiolation; iodination